THE EFFECT OF LEADERSHIP, INTERPERSONAL COMMUNICATION AND WORK DISCIPLINE ON THE PERFORMANCE OF HIGH SCHOOL TEACHERS IN THE DISTRICT OF WEST PEMULUTAN OGAN ILIR, SOUTH SUMATRA - Burmansyah Burmansyah; Herman Seri; Diah Isnaini Asiati (KOLEGIAL, 2020)
This study aims to determine the Effect of Leadership, Interpersonal Communication and Work Discipline on the Performance of High School/Vocational Teachers in the District of West Pemulutan Ogan Ilir, South Sumatra. This research is associative research, aims to see the significance of the influence of independent variables (X), namely Leadership (X1), Interpersonal Communication (X2) and Work Discipline (X3) and the dependent variable Teacher Performance (Y). The population is 70 teachers as respondents for the research sample. Sampling is done using the Saturated Sampling technique, which is taken as a whole from the population. Simultaneously Leadership, Interpersonal Communication and Work Discipline variables have a positive and very significant influence on the performance of high school / vocational school teachers in the West Pemulutan District Ogan Ilir. The correlation coefficient number is obtained by Pearson correlation number of 0.798, meaning that between Leadership, Interpersonal Communication and Work Discipline together with Teacher Performance correlates quite strongly. The results of the study are that there is a significant influence of Leadership, Interpersonal Communication, and Work Discipline jointly on the Performance of High School / Vocational Teachers in the West Pemulutan District, Ogan Ilir, also leadership provides a considerable boost in the process of improving the efficiency and effectiveness of quality performance of institutions especially education.